IMPLEMENTASI MODEL PEMBELAJARAN STEAM TERHADAP MINAT BELAJAR SISWA - Agnes Sirinding; Mustika Irianti; Anis Alfian Fitriani (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
The objective of this study is to ascertain the impact of the STEAM learning model on the learning interests of fifth-grade students in the science subject of SD Inpres 14 Sorong Regency. The research design is experimental, employing a one-group pretest-posttest design. The sample size for this study was 10 students. The data were collected through observation, the administration of learning interest questionnaires, and the examination of relevant documentation. The data analysis techniques included a validity test, a reliability test, a normality test, and a hypothesis test. The results of the reliability test Cronbach's Alpha of the pretest instrument was 0.794 and exceeded the alpha value of 0.794 > 0.6. Thus, the questionnaire instrument is said to be reliable because it has met the requirements. The normality test of the pretest learning outcomes of grade V students has a significance of 0.879 > 0.05 while the post-test has a significance of 0.209 > 0.05. The hypothesis test obtained ????ℎ????????????????????of 12,150 with dk = n – 1 (10-1 = 9) obtained ????????????????????????  2.262 sig results (2-tailed) of 0.000. Based on the results, the value of 0.000 is less than 0.05 where 0.000 < 0.05. The results of this test indicate that the alternative hypothesis (H₁) is accepted and the null hypothesis (H₀) is rejected. It can thus be concluded that the STEAM learning model has significance on students' interest in learning science subjects in class V of SD Inpres 14 Sorong Regency.